Pandawa Seraja (Pramuka Mawas Bencana Sehat Raga dan Jiwa) in SMP Negeri 2 Martapura Timur Banjar Regency - Neka Erlyani; Vina Yulia Anhar; Ihya Hazairin Noor; Zuhrufa Wanna Yolanda; Devi Damayanti; Nuraida Nuraida (Lambung Mangkurat, 2023)
Floods are the most frequent disasters globally and cause significant impacts and losses. One of the impacts is psychological impact in the form of fear and anxiety. One-third of the victims were children which can result in psychological